PABRIK GULA CEPIRING KENDAL PASCA NASIONALISASI TAHUN 1957-2008 - Farida, Lina (Journal of Indonesian History, 2014)
Sugar contains a lot of interesting things to be studied and not widely known yet by the layman. In addition its relation to the roots of nationality, Sugar also became the way to come to a modern civilization in Javanese colonialism. The purpose of this study is used to determine the state of the Cepiring Sugar Factory in a Dutch colonial period and its post-nationalization years development from 1957 to 2008. The methods in this study are based on historical research methods, they are; (1) heuristics, (2) a source of criticism, (3) interpretation, and (4) historiography. Techniques that used to get the source is by do observation, interviews, documentation, literature studies, and docu-ments studies. The results of this research are the changes that undergone by Cepiring Sugar Facto-ry after the nationalization of foreign factory that owned by the Dutch in 1957, the one of it is the changes in management system. This factory has encountered several vacuums. First, in 1904-1916 because of World War I, the second is in 1930-1935 because of economic crisis, the third in 1942-1954 because of function changing by the Japanese, and in 1998-2008 because of financial crisis. However, by improved management and great effort, Cepiring Sugar Factory can be operating un-til now.Â Industri gula merupakan suatu hal yang menarik untuk dikaji dan belum banyak diketahui oleh orang awam. Selain berhubungan erat dengan akar-akar kebangsaan, gula juga menjadi pembuka peradaban modern di Jawa era kolonial. Tujuan dari penelitian ini adalah untuk mengetahui keadaan Pabrik Gula Cepiring masa Kolonial Belanda dan perkembangannya pasca nasionalisasi tahun 1957-2008. Metode dalam penelitian ini berdasarkan metode penelitian sejarah, yaitu (1) heuristik, (2) kritik sumber, (3) interpretasi, dan (4) historiografi. Teknik mendapatkan sumber, peneliti lakukan dengan observasi, wawancara, dokumentasi, studi pustaka, dan studi dokumen. Hasil penelitian ini yaitu Pabrik Gula Cepiring banyak mengalami perubahan setelah adanya na-sionalisasi perusahaan-perusahaan asing milik Belanda tahun 1957, salah satunya perubahan pada sistem manajemen. Pabrik ini telah beberapa kali mengalami kevakuman. Pertama yaitu tahun 1904-1916 akibat Perang Dunia I, kedua yaitu tahun 1930-1935 akibat krisis ekonomi, ketiga yaitu tahun 1942-1954 karena dialihfungsikan oleh Jepang, dan tahun 1998-2008 karena krisis moneter. Akan tetapi dengan perbaikan manajemen serta usaha yang keras, Pabrik Gula Cepiring dapat beroperasi kembali sampai saat ini.